2009
DOI: 10.1007/s00415-009-5015-8
|View full text |Cite
|
Sign up to set email alerts
|

Specific electron transport chain abnormalities in amyotrophic lateral sclerosis

Abstract: In an amyotrophic lateral sclerosis (ALS) patient who also had an IgA gammopathy, autopsy studies identified the IgA in the surviving motor neurons. Further, the IgA bound the surface of isolated bovine motor neurons and inhibited neuronal proliferation in culture. To determine the pathologic basis of this IgA interaction with motor neurons, a neuroblastoma cDNA library was generated and screened with the IgA monoclonal antibody. Reactive clones were identified as flavin adenine dinucleotide (FAD) synthetase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 25 publications
(30 reference statements)
2
21
0
Order By: Relevance
“…Our analysis revealed that respiratory chain components decreased expression during spMN maturation, consistent with observations in ALS patient blood [44]. Additionally, DNA repair pathways decreased expression as spMNs mature, suggesting a reduced ability to mitigate oxidative DNA damage.…”
Section: Discussionsupporting
confidence: 88%
“…Our analysis revealed that respiratory chain components decreased expression during spMN maturation, consistent with observations in ALS patient blood [44]. Additionally, DNA repair pathways decreased expression as spMNs mature, suggesting a reduced ability to mitigate oxidative DNA damage.…”
Section: Discussionsupporting
confidence: 88%
“…The corresponding products differ from each other at either the N-or C-terminal region, with the longest one being isoform 1, localized in mitochondria (8,23). A FADS migrating on SDS-PAGE with a molecular mass of 65 kDa was also identified in human neurons (26). Different from humans, only a single transcript corresponding to a predicted product of 490 amino acids (54.6 kDa) is at the moment reported for rats in Ensembl (accession number ENSRNOP00000028030) and NCBI Entrez gene (gene identifier 751787.)…”
Section: Discussionmentioning
confidence: 98%
“…Other post-translational modifications were not predicted (i.e., O-glycosylations) or predicted with a low probability (i.e., sumoylation, using both the SUMOplot TM analysis program and Sumosp 2.0 software (56)). Tissue distribution and subcellular localization of these isoforms are still uncharacterized (8,26) and represent one of the ongoing research efforts in our laboratory. Whatever the isoform details, to our knowledge this is the first evidence that FAD synthesis occurs in the nucleus, and we postulate that, as hypothesized by others (27), this event could be linked to the biogenesis and flavinylation of nuclear flavoproteome (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cases of ALS have been described as a mitochondriopathy (Finsterer, 2002(Finsterer, , 2003 including a mitochondrial DNA www.intechopen.com mutation in the gene encoding subunit I of the mitochondrial respiratory chain complex IV (Comi et al, 1998). The electron transport chain proteins FAD synthetase, riboflavin kinase, cytochrome C1, and succinate dehydrogenase complex subunit B expression were significantly decreased in some ALS patients (Lin et al, 2009). In the mSOD1 mice or cell culture familial ALS model, complexes I, II and IV of the electron transport chain exhibit decreased enzyme activities, even at early stages of the disease Mattiazzi et al, 2002;Menzies et al, 2002a,b).…”
Section: Wwwintechopencommentioning
confidence: 99%